The Implementation of the Demonstration Method in Playing the Bonang Musical Instrument in Extracurricular Activities at SMA Negeri Tolisu - Arifin, Zainal; Rahmawati Ohi; Trubus Semiaji (The Future of Education Journal, 2026)
This study is motivated by the challenges encountered in the degung gamelan music extracurricular activities at SMA Negeri Tolisu, particularly the mismatch between students’ techniques and the correct playing patterns of the bonang musical instrument. Students still require full instruction and intensive supervision due to inefficiencies in the practice process, which in turn affect their creativity and interest in music. The purpose of this study is to describe the implementation of the demonstration method in improving students’ ability to play the bonang among extracurricular participants. This research adopts a descriptive qualitative approach, supported by simple quantitative analysis to process students’ learning outcome data. The research subjects consisted of eight students from SMA Negeri Tolisu. Data collection techniques included unstructured interviews, direct field observation, and documentation in the form of photographs and videos of the activities. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that the implementation of the demonstration method over eight meetings led to significant improvement in students’ abilities. The learning process comprised preparation, implementation (introduction, demonstration, guided practice, independent practice), and evaluation stages. Based on an assessment rubric covering cognitive, affective, and psychomotor aspects, most students achieved the “Good” category, with achievement percentages exceeding the predetermined indicator of 75%. In conclusion, the demonstration method is effective in improving students’ skills in playing the bonang musical instrument, as it allows students to directly observe and imitate the techniques.